An evaluation of the textbook “Kid’s Box 5” for grade 5 at Doan Thi Diem Private Primary School = Nghiên cứu đánh giá sách giáo khoa Kid's Box 5" dùng cho học sinh lớp 5 tại trường Tiểu học Dân lập Đoàn Thị Điểm - Đỗ, Thị Thuần (University of Languages and International Studies, 2017)
Materials evaluation is important in language teaching and learning and it is necessary to evaluate materials frequently. This study is conducted to evaluate the appropriateness of the textbook “Kid’s Box 5” (by Caroline Nixon & Michael Tomlinson, Cambridge University Press, 2010 ) which has been in used for students in Doan Thi Diem Private Primary School (DTDS) since 2011. To evaluate the appropriateness of the textbook to the students’ needs and objectives of the course, document analysis and questionnaires from the perspectives of teachers and students of DTDS in term of aims, design and organization, content and methodology were used. The study adopted model by Hutchinson and Waters (1987) in which objective and subjective analysis were done to achieve the results of the study. The findings of the study reveal that the textbook could be suitable to the students and course requirements in terms of objectives, design and organization, topics, vocabulary, listening, reading and speaking components. The textbook in general is appropriate to the students’ needs and the course requirements. However, the tasks and exercises in grammar, writing and pronunciation sections need improving. Based on the findings, the thesis suggests that adaptation should be made to overcome some weaknesses in order to enhance the effectiveness of the book for future use